The effects of aquatic therapy on mobility of individuals with neurological diseases: a systematic review. (August 2015) - Marinho-Buzelli, Andresa R; Bonnyman, Alison M; Verrier, Mary C
Objective: To summarize evidence on the effects of aquatic therapy on mobility in individuals with neurological diseases. Data sources: MEDLINE, EMBASE, PsycInfo, CENTRAL, CINAHL, SPORTDiscus, PEDro, PsycBITE and OT Seeker were searched from inception to 15 September 2014. Hand-searching of reference lists was performed in the selected studies. Review methods: The search included randomized controlled trials and quasi-experimental studies that investigated the use of aquatic therapy and its effect on mobility of adults with neurological diseases. One reviewer screened titles and abstracts of retrieved studies from the search strategy. Two reviewers independently examined the full texts and conducted the study selection, data extraction and quality assessment. A narrative synthesis of data was applied to summarize information from included studies. The Downs and Black Scale was used to assess methodological quality. Results: A total of 116 articles were obtained for full text eligibility. Twenty studies met the specified inclusion criteria: four Randomized Controlled Trials (RCTs), four non-randomized studies and 12 before-and-after tests. Two RCTs (30 patients with stroke in the aquatic therapy groups), three non-randomized studies and three before-and-after studies showed "fair" evidence that aquatic therapy increases dynamic balance in participants with some neurological disorders. One RCT (seven patients with stroke in the aquatic therapy group) and two before-and-after tests (20 patients with multiple sclerosis) demonstrated "fair" evidence on improvement of gait speed after aquatic therapy. Conclusion: Our synthesis showed "fair" evidence supporting the use of aquatic therapy to improve dynamic balance and gait speed in adults with certain neurological conditions.